Obama's legacy and beyond. Issue 3 (December 2016) - Anderson, Elizabeth; Purdy, Jedediah; Moyn, Samuel; Yeselson, Richard; Bruenig, Elizabeth; Kenworthy, Lane; Garman, Joss; Finlayson, Alan; Azari, Julia; Shenk, Timothy
Abstract : Leading journalists and academics from both sides of the Atlantic review Obama's presidency and legacy and look ahead to Trump's term in the most powerful office in the world.